Pregnancy-associated Plasma Protein-A Regulates Myoblast Proliferation and Differentiation through an Insulin-like Growth Factor-dependent Mechanism - Kumar, Ashok (2005)
Pregnancy-associated plasma protein-A (PAPP-A), a member of the metalloproteinase superfamily, is an important regulator of mammalian growth and development. However, the role of PAPP-A and its mechanism of action in various cellular processes remain unknown. In this study, we have investigated the role of PAPP-A in skeletal myogenesis using C2C12 myoblasts. Recombinant PAPP-A was purified from the conditioned medium of HT1080 cells overexpressing PAPP-A. Treatment of C2C12 myoblasts with PAPP-A increased their proliferation in a dose- and time-dependent manner. Addition of exogenous PAPP-A also increased the myotube formation and the activity of creatine kinase in C2C12 cultures. Transient overexpression of the full-length PAPP-A-(1–1547), but not truncated protease-inactive N-terminal PAPP-A-(1–920) or C-terminal PAPP-A-(1100–1547), significantly enhanced the proliferation of C2C12 myoblasts. In vitro and in situ experiments demonstrated that PAPP-A cleaves insulin-like growth factor-binding protein (IGFBP)-2, but not IGFBP-3, in the conditioned medium of C2C12 myoblasts. Overexpression of PAPP-A led to degradation of the IGFBP-2 produced by C2C12 myoblasts and increased free IGF-I concentrations without affecting total IGF-I concentrations. Addition of protease-resistant IGFBP-4 completely abolished the PAPP-A-induced proliferation of C2C12 myoblasts. Our results demonstrate that 1) PAPP-A increases the proliferation and differentiation of myoblasts, 2) the stimulatory effect of PAPP-A on myogenesis is governed by its proteolytic activity, and 3) PAPP-A promotes skeletal myogenesis by increasing the amount of free IGFs via specific degradation of IGFBP-2 produced by myoblasts.